2022
DOI: 10.2109/jcersj2.21155
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses of amorphous calcium carbonate before and after removing strontium ions from an aqueous solution

Abstract: Amorphous calcium carbonate (ACC) is a precursor of crystalline calcium carbonate; hence, its structural information at the atomic level is very important for controlling the morphology of crystalline calcium carbonate. In this study, we attempted to elucidate the process of Sr extraction from aqueous solution by using ACC for the purpose of removal of radioactive Sr from the contaminated water leaked after the Fukushima Daiichi nuclear accident. The pair distribution functions, g(r) obtained by X-ray and neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
6
6
0
Order By: Relevance
“…The measured ACC density is within the previously reported range of 1.6 to 2.4 g/cm 3 and is within error of the measurements of Cobourne et al (2.19 g/cm 3 for Ca 0.95 Mg 0.05 CO 3 ·0.25H 2 O) and Fernandez-Martinez et al (2.18 g/cm 3 for unknown n ) . Our measured ACC density is above that of Shuseki et al (2.10 g/cm 3 for n = 1.0), lower than those measured by Jensen et al (2.28 g/cm 3 for n = 1.1 and 2.43 g/cm 3 for n = 0.5), and lower than those of the hydrated crystalline calcium carbonate phases monohydrocalcite (2.42 g/cm 3 for n = 1) and calcium carbonate hemihydrate (2.39 g/cm 3 for n = 0.5) . All of these ex situ values are significantly higher on average than the very low values (∼1.6 g/cm 3 ) measured in situ . , No density values have been published for ASC, and the only known pure Sr carbonate phase is strontianite with a density of 3.84 g/cm 3 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The measured ACC density is within the previously reported range of 1.6 to 2.4 g/cm 3 and is within error of the measurements of Cobourne et al (2.19 g/cm 3 for Ca 0.95 Mg 0.05 CO 3 ·0.25H 2 O) and Fernandez-Martinez et al (2.18 g/cm 3 for unknown n ) . Our measured ACC density is above that of Shuseki et al (2.10 g/cm 3 for n = 1.0), lower than those measured by Jensen et al (2.28 g/cm 3 for n = 1.1 and 2.43 g/cm 3 for n = 0.5), and lower than those of the hydrated crystalline calcium carbonate phases monohydrocalcite (2.42 g/cm 3 for n = 1) and calcium carbonate hemihydrate (2.39 g/cm 3 for n = 0.5) . All of these ex situ values are significantly higher on average than the very low values (∼1.6 g/cm 3 ) measured in situ . , No density values have been published for ASC, and the only known pure Sr carbonate phase is strontianite with a density of 3.84 g/cm 3 .…”
Section: Resultssupporting
confidence: 89%
“…The densities thus determined are 2.19 ± 0.04 g/cm 3 for ACC and 2.97 ± 0.05 g/cm 3 for ASC. The measured ACC density is within the previously reported range of 1.6 to 2.4 g/cm 3 and is within error of the measurements of Cobourne et al (2.19 g/cm 3 for Ca 0.95 Mg 0.05 CO 3 ·0.25H 2 O) and Fernandez-Martinez et al (2.18 g/cm 3 for unknown n ) . Our measured ACC density is above that of Shuseki et al (2.10 g/cm 3 for n = 1.0), lower than those measured by Jensen et al (2.28 g/cm 3 for n = 1.1 and 2.43 g/cm 3 for n = 0.5), and lower than those of the hydrated crystalline calcium carbonate phases monohydrocalcite (2.42 g/cm 3 for n = 1) and calcium carbonate hemihydrate (2.39 g/cm 3 for n = 0.5) .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Cobourne et al 62 reported a much less dense ACC (2.19 g cm −3 for n = 0.25 using He pycnometry). Shuseki et al 63 synthesized ACC with n = 1 and reported a density of 2.1 g cm −3 (measured by pycnometry with unreported gas). Other estimates using small-angle X-ray scattering (SAXS) 64 and amplitude contrast analysis of transmission electron micrographs 65 have found very low values around 1.6 g cm −3 .…”
Section: Resultsmentioning
confidence: 99%
“…Given that the previous modeling, aqueous geochemical, and microscopic analyses suggested the potential association of Sr 2+ with CaCO 3 mineralization, the local environment of various Sr 2+ -incorporated calcium carbonate phases was used to inform the fits to the spectra. 41,45,50,101,102 The untreated PPQ system returned a spectrum that was best fit with 9 O atoms at 2.6 Å indicative of outer-sphere adsorption. 81,103,104 The best fit to the spectrum from the PPQ sample indicated a central Sr atom in 8-fold coordination (8 O atoms at 2.53 Å) with an addition of 4 C atoms at 2.95 Å.…”
Section: ■ Introductionmentioning
confidence: 99%